Futsal injuries: A 7-season incidence and characteristics - Yoshida, K.; Tateishi, T.; Morimoto, Y. (Journal of Science and Medicine in Sport Plus, 2023)
Objectives Most literatures describe the injury incidence in futsal during the matches, however, the true injury incidence in matches and trainings through the season is unclear.